The (p)ppGpp synthetase Rsh promotes rifampicin tolerant persister cell formation in Brucella abortus by regulating the type II toxin-antitoxin module mbcTA - Liu, Xiaofang; Wang, Pingping; Yuan, Ningqiu; Zhai, Yunyi; Yang, Yuanhao; Hao, Mingyue; Zhang, Mingxing; Zhou, Dong; Liu, Wei; Jin, Yaping; Wang, Aihua (Frontiers in Microbiology, 2024)
Persister cells are transiently tolerant to antibiotics and are associated with recalcitrant chronic infections due to recolonization of host cells after antibiotic removal. Brucella spp. are facultative pathogens that establish intracellular infection cycles in host cells which results in chronic persistent infections. Brucella abortus forms multi-drug persister cells which are promoted by the (p)ppGpp synthetase Rsh during rifampicin exposure. Here, we confirmed that Rsh promoted persister cells formation in B. abortus stationary phase treated with rifampicin and enrofloxacin. Deletion of the gene for Rsh decreased persister cells level in the presence of these drugs in different growth phases. However, persister cells formation by deletion strain varied in different growth phases in the presence of other antibiotics. Rsh also was involved in persister cells formation during rifampicin treatment under certain stress conditions, including acidic conditions, exposure to PBS, and heat stress. Moreover, Rsh impacted persister cell levels during rifampicin or enrofloxacin treatment in RAW264.7 macrophages. Certain typeIItoxin-antitoxin modules were upregulated under various stress conditions in B. abortus. We established that Rsh positively regulated the type II toxin-antitoxin mbcTA. Moreover, rifampicin-tolerant persister cells formation was elevated and ATP levels were decreased when mbcTA promoter was overexpressed in Rsh deletion background in stationary phase. Our results establish that (p)ppGpp synthetase Rsh plays a key role in B. abortus persistence and may serve as a potent novel target in combination with rifampicin in the development of new therapeutic approaches and prevention strategies to treat chronic infections of Brucella.